Relating Carbon Dioxide Emissions with Macroeconomic Variables in the Philippine Setting - Palanca-Tan, Rosalina (Archīum Ateneo, 2016)
Using cointegration and error correction modeling techniques, this paper examines the dynamics of carbon dioxide (CO2) emissions in relation to economic growth, energy consumption, trade openness, urbanization and foreign direct investments in the case of the Philippines. The study finds that 1) economic growth and CO2 emissions have a significant positive linear relationship, suggesting that income growth policies must be subject to reasonably stringent environmental constraints related to CO2 emissions; 2) CO2 emissions are inelastic with respect to energy use in the short run, but its response becomes elastic in the long-run; and 3) CO2 emissions have a positive elasticity with respect to FDI which conforms with the Pollution Haven hypothesis.